Guyana. Significant achievements 2016 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The main activities carried out by the Institute in Guyana during 2016 are identified, with respect to the needs and interests of the country, strengthening issues such as risk management, water harvesting, economy, drought management, manuals, quality of life, resilience against climate change, pest and disease control. It also supported the control of human diseases, antimicrobial resistance, food control, safety through the Codex Alimentarius. Finally, work was carried out on the management of the control of the fruit fly and in the value chains of carambola, birds and small ruminants.